Use of reflectance interference contrast microscopy to characterize the endothelial glycocalyx stiffness - Job, Kathleen M. (American Physiological Society, 2012)
Reflectance interference contrast microscopy (RICM) was used to study the mechanics of the endothelial glycocalyx. This technique tracks the vertical position of a glass microsphere probe that applies very light fluctuating loads to the outermost layer of the bovine lung microvascular endothelial cell (BLMVEC) glycocalyx. Fluctuations in probe vertical position are used to estimate the effective stiffness of the underlying layer. Stiffness was measured before and after removal of specific glycocalyx components. The mean stiffness of BLMVEC glycocalyx was found to be ∼7.5 kT/nm(2) (or ∼31 pN/nm). Enzymatic digestion of the glycocalyx with pronase or hyaluronan with hyaluronidase increased the mean effective stiffness of the glycocalyx; however, the increase of the mean stiffness on digestion of heparan sulfate with heparinase III was not significant. The results imply that hyaluronan chains act as a cushioning layer to distribute applied forces to the glycocalyx structure. Effective stiffness was also measured for the glycocalyx exposed to 0.1%, 1.0%, and 4.0% BSA; glycocalyx compliance increased at two extreme BSA concentrations. The RICM images indicated that glycocalyx thickness increases with BSA concentrations. Results demonstrate that RICM is sensitive to detect the subtle changes of glycocalyx compliance at the fluid-fiber interface.